Common Sense, Plain Sense, and Faithful Dissent: Evangelical Interpretation and the Ethics of Marriage Equality - Clifton-Soderstrom, Michelle (Journal of the Society of Christian Ethics, 2017)
This essay constructs a moral theology of reading scripture by retrieving habits and virtues of early evangelical readers that have potential to help evangelicals reengage one another on divisive topics such as marriage equality. I use this moral theology of reading scripture to diagnose power dynamics operative in commonsense assumptions around gender and plain-sense interpretive frameworks that privilege literal interpretations. I interact with the historical trajectory of evangelicalism that values conversion as the telos of reading scripture. Continental Pietists also read in a spirit of faithful dissent, allowing them to cast the interpretive net widely, to welcome new readers, and to challenge social barriers that excluded marginalized voices. Faithful dissent is a necessary habit that generates courage to be open to the Spirit's work of blessing and renewal in the world.